2009
DOI: 10.15288/jsad.2009.70.106
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Lagged Evaluation of Eating Disorder Symptomatology and Substance-Use Problems

Abstract: ABSTRACT. Objective: The purpose of this study was to conduct a temporal examination of the associations among disordered eating behaviors, substance use, and use-related negative consequences in female college students-a population at high risk for developing eating and substance-use disorders. Method: Participants completed assessments of disordered eating behaviors, alcohol and drug use, and use-related negative consequences. Results: Results support previous research suggesting that disordered eating behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 55 publications
3
12
0
2
Order By: Relevance
“…Unique to this study was identification of associations between specific patterns of EDs, alcohol use, and negative consequences: AN and BN were significantly associated with binge drinking and alcoholrelated problems while BED was not associated with either alcohol outcome. Consistent with previous research (e.g., Dunn et al, 2008), disordered eating, particularly BN symptoms, accounted for more variance in alcohol-related problems than binge drinking. Symptoms of AN and BN (e.g., purging, fasting) may cause women who drink to reach higher BACs faster due to accelerated alcohol absorption related to lack of food or having a lower BMI, which can result in numerous negative consequences (e.g., vomiting, impairments in gross motor control, alcohol poisoning) (Hamilton, 2009).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Unique to this study was identification of associations between specific patterns of EDs, alcohol use, and negative consequences: AN and BN were significantly associated with binge drinking and alcoholrelated problems while BED was not associated with either alcohol outcome. Consistent with previous research (e.g., Dunn et al, 2008), disordered eating, particularly BN symptoms, accounted for more variance in alcohol-related problems than binge drinking. Symptoms of AN and BN (e.g., purging, fasting) may cause women who drink to reach higher BACs faster due to accelerated alcohol absorption related to lack of food or having a lower BMI, which can result in numerous negative consequences (e.g., vomiting, impairments in gross motor control, alcohol poisoning) (Hamilton, 2009).…”
Section: Discussionsupporting
confidence: 89%
“…The co-occurrence of alcohol use and EDs may be explained by shared, predisposing, personality characteristics (Dunn, Neighbors, Fossos, & Larimer, 2008) such as the Big Five traits (McCrae & Costa, 1987) of high neuroticism, extraversion, and openness to experience, and low conscientiousness and agreeableness (Cassin & von Ranson, 2005;Ellickson-Larewa, Naragon-Gainey, & Watson, 2013;Kuntsche, Knibbe, Gmel, & Engels, 2006). While presented rather concisely here, results of studies assessing personality in relation to EDs and alcohol outcomes tend to yield complex and inconsistent results, making firm conclusions about the relationships difficult.…”
Section: Introductionmentioning
confidence: 81%
“…Why those with higher education level would have a higher likelihood of BED is unclear, but given that it was an independent predictor of BED it warrants further investigation. The association between symptoms of alcohol use disorder and BED found in this study (i.e., 65% greater odds of BED among those with alcohol problems) has also been documented in a study of female college students . However, this association was not found in another cohort of bariatric surgery candidates, and importantly, our prior work found no increased risk of postoperative alcohol problems related to preoperative BED status .…”
Section: Discussionsupporting
confidence: 69%
“…Although we know of no previous study of the relative sizes of cross-lagged ORs between eating disorders and other mental disorders, one cross-lagged evaluation of eating behaviors and substance-use problems revealed no concurrent or temporal associations between binge eating symptoms and alcohol or illicit substance use (104). In addition, two separate papers from one prospective study (101,103) found other mental disorders predicting eating disorders somewhat more strongly than vice-versa.…”
Section: Discussionmentioning
confidence: 99%